DAYAK KENYAH CULTURAL RESEARCH PLANNING IN SAMARINDA EMPLOYMENT ON THE VIEW OF CONTEMPORARY BUILDING: PERENCANAAN RISET KEBUDAYAAN DAYAK KENYAH DI SAMARINDA PENEKANAN PADA TAMPILAN BANGUNAN KONTEMPORER - Cisyulia Octavia HS; Darius Shyafary (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2021)
This study aims to design a Dayak Kenyah Cultural Research Center in Samarinda's Pampang Cultural Village using an emphasis on the appearance of contemporary Kenyah Dayak buildings and spatial organization. The benefits of this research resulted in a Cultural Research Center with good spatial planning and circulation and a place of education about Dayak Kenyah culture for the general public. The research method used is descriptive analytic and synthesis analysis with data collection techniques using observation techniques from observing facts in the field, interviews, and analysis of documents from literature studies related to the design concept of Dayak Kenyah Cultural Research Center. The results of the study are in the form of designing facilities by adjusting contemporary ethnic designs on building facades that provide elements of Dayak Kenyah cultural values such as adjusting the color of buildings to the typical colors of Dayak Kenyah culture and paying attention to the spatial planning in buildings used as places for cultural activities and research on Dayak Kenyah culture.